The Effect of ABCB1 and CES1 Polymorphisms on Plasma Levels of Dabigatran and Risk of Hemorrhagic Complications in Ischemic Stroke Patients - Olšerová, Anna; Janský, Petr; Magerová, Hana; Šrámková, Tereza; Kešnerová, Petra; Kmetonyová, Silvia; Šulc, Vlastimil; Halmová, Hana; Šrámek, Martin; Šarbochová, Ivana; Paulasová-Schwabová, Jaroslava; Benešová, Kateřina; et al. (American journal of therapeutics, 2024)
BACKGROUND: Dabigatran directly inhibits thrombin and is used in primary and secondary stroke prevention in individuals with nonvalvular atrial fibrillation. The prodrug dabigatran etexilate is absorbed by enteral P-glycoprotein (ABCB1) and then activated by hepatic and intestinal carboxylesterases (CES1) to produce active metabolites. Variations in dabigatran metabolism because of genetics may affect concentration levels and clinical outcomes. STUDY QUESTION: We conducted a study to assess how polymorphisms in the CES1 (rs2244613) and ABCB1 (rs4148738) genes affect the through plasma level (c min ) of dabigatran and its correlation to clinical outcomes. STUDY DESIGN: Retrospective multicentric study of consecutive patients on dabigatran therapy. Examination of CES1 rs2244613 and ABCB1 rs4148738 polymorphisms, c min 12 hours after administration, clinical follow-up (ischemic stroke, major or clinically relevant hemorrhage, myocardial infarction, other thromboembolism, and death). MEASURES AND OUTCOMES: A total of 432 patients received treatment for an average of 19.78 months (SD of 20.165). The sex distribution of the patients was 56.5% male, and the average age was 67.56 years (SD of 14.7). The ABCB1 variant genotype was present in 67.8% of patients, whereas 37.5% carried the CES1 polymorphism. RESULTS: Compared with wild-type patients, patients with the CES1 variant had significantly lower dabigatran plasma levels (with a mean difference of 16.986; 95% confidence interval, 5.794-28.178 ng/mL, P = 0.003). We also found a significant risk of major bleeding in patients carrying the ABCB1 rs4148738 allele (hazard ratio = 1.99, confidence interval 95% 1.10 to 3.59, P = 0.024). CONCLUSIONS: The CES1 variant genotype rs2244613 is closely linked with reduced c min of dabigatran. Carriers of the ABCB1 rs4148738 polymorphism exhibit a tendency toward higher plasma levels of dabigatran, which leads to a significantly increased risk of bleeding.
Keywords: dabigatran; Hemorrhage; karboxylesterhydrolasy; senioři nad 80 let; Dabigatran; krvácení; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; antitrombiny; ischemická cévní mozková příhoda; fibrilace síní; P-glykoproteiny; Ischemic Stroke; Carboxylic Ester Hydrolases; mužské pohlaví; Antithrombins; ženské pohlaví; ATP Binding Cassette Transporter, Subfamily B; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; Atrial Fibrillation; Aged; senioři; Male; Retrospective Studies; Female